A new genus and species of delphacid planthopper (Hemiptera: Fulgoroidea: Delphacidae) from Central America with a preliminary regional species list - Bartlett, Charles R.; Kunz, Gernot (Zootaxa, 2015)
The new genus Ampliphax, assigned to the Delphacini, is described and illustrated with a single new species A. grandis from Costa Rica and Panama. Ampliphax grandis is a large species with a projected head. DNA barcode data suggest, among currently barcoded taxa, an affinity to the genus Bostaera. A checklist of the delphacid species from Costa Rica, Panama, and Nicaragua based on literature and specimen records is provided.